Scientific Authority in Crisis: A Dialogical Reflection between Bruno Latour and Syed Muhammad Naquib Al-Attas in The Post-Truth Era - Rahmad Tri Hadi; Rido Putra; Zaim Rais (IAIN SYEKH NUR JATI, 2025)
ABSTRACT: In this article, the crisis of authority of science in the post-truth era is analyzed in a dialogical reflection between the science studies of Bruno Latour and the Islamic metaphysics of Syed Muhammad Naquib al-Attas. The context of the investigation is rooted in the challenge of public confidence in science, hoax information, as well as the rising impact of ideology rather than facts in decision-making. This article has a twofold purpose: first, to analyze with a comparative-hermeneutic dialogical approach the works of Latour and al-Attas, considering both philosophical backgrounds despite differences in scholarship, in relation to the challenge of science credibility; second, considering an in-depth review of both Latour’s science studies and al-Attas’ metaphysical thinking in an Islamic context. Articles in refereed journals, books, among other literature sources focusing on science education, science epistemology, as well as literature on Islamic thought, have been used in analyzing information in this article. The results of the analysis have shown commonalities between both Latour’s perspectives and al-Attas’ metaphysical thoughts in relation to a new vision emphasizing the reintegration of science into a metaphysical view. Latour requires a reassembly of science through the agency of a network model of socio-material actors, whereas al-Attas promotes the Islamization of knowledge on the basis of ta’dib and the Islamic worldview. In the conclusion, the current paper finds that there is a potential for a more nuanced and holistic approach through the dialogical encounter between the two models for addressing the problem of the crisis in the legitimation of science.ABSTRAK: Artikel ini mengkaji krisis epistemologis otoritas sains di era post-truth melalui refleksi dialogis antara studi sains Bruno Latour dan metafisika Islam Syed Muhammad Naquib al-Attas. Latar belakang penelitian ini adalah merosotnya kepercayaan publik terhadap sains, maraknya misinformasi (hoax), serta meningkatnya pengaruh narasi ideologis dan emosional dibandingkan bukti empiris. Tujuan penelitian ini adalah untuk menelusuri bagaimana Latour dan al-Attas, meskipun berasal dari tradisi filsafat yang sangat berbeda, secara kritis merespons krisis kredibilitas sains dan menawarkan kerangka epistemologis alternatif. Dengan menggunakan metode hermeneutik-dialogis dan komparatif, kajian ini menganalisis karya-karya utama kedua pemikir tersebut yang dikontekstualisasikan melalui literatur kontemporer tentang pendidikan sains, epistemologi, dan pemikiran Islam. Data penelitian diperoleh dari jurnal ilmiah, buku, dan literatur lainnya yang membahas pendidikan sains, krisis post-truth, dan Islamisasi ilmu. Temuan penelitian menunjukkan bahwa baik Latour maupun al-Attas sama-sama mengkritik modernitas dan menekankan pentingnya mengembalikan sains ke dalam kerangka etika dan metafisika yang lebih luas. Latour menyerukan penyusunan ulang sains melalui jaringan aktor sosial-material, sementara al-Attas menggagas Islamisasi ilmu yang berlandaskan pada ta’dib dan pandangan hidup Islam. Artikel ini menyimpulkan bahwa pertemuan dialogis antara kedua kerangka ini dapat menawarkan respons yang lebih kaya dan holistik terhadap krisis legitimasi sains, serta mengarah pada epistemologi yang tidak hanya menekankan pengetahuan, tetapi juga kebijaksanaan dan makna.